WACANA KOMPAS TERHADAP PEMBERITAAN MUKTAMAR NU KE-33 DAN MUHAMMADIYAH KE-47 - Lilis Sarifatul Ajariyah; Agus Sriyanto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2016)
In August 2015, there are two major Islamic organizations in Indonesia, NU and Muhammadiyah held a consultative forum which is the highest in the conference organization. 33 NU congress held in Jombang, East Java began 1 to 5 August 2015. As at August 3 to 7 held 47 Muhammadiyah congress in Makassar, South Sulawesi. One of the print media that provide accounts is Kompas. Interestingly, Kompas has a history as the founder of the mass media-founders are Catholic figures. As P. K. Ojong, Oetama, R. G. Doeriat, Frans Xaverius Seda, Polycarp Swantoro, R. Soekarsono, there are also representatives of the Supreme Council of hierarchical elements of the Indonesian Bishops (Mawi), Catholic party Union of Catholic University Students of the Republic of Indonesia (PMKRI). Kompas discourse about NU and Muhammadiyah that are the focus of research. How the two types of the news media is manufactured into a text. Because the media really is in the middle of a social reality that is loaded with a variety of interests, but has been linked with the social reality. As Aart Van Zoest once said, that a text has never been separated from ideology and have the ability to manipulate the reader toward an ideology. In the text of the media, reporters, also the editor, full power over the choice of words to beworn. He may or must select one word in between the rows of words that are quite similar yet different â€œflavorsâ€ of his. This research is a library (library research) with a focus on the study of print media ie newspapers Kompas, while the object to be studied is the preaching of NU and Muhammadiyah 33rd to 47th. In conducting the study, researchers used a discourse analysis approach Norman Fairclough. Fairclough focused discourse on language. Therefore, this analysis will focus on how it is formed and shaped the language of social relationships and social context. From this analysis, there are three points which were highlighted by researchers that democracy, state, and religious. Based on these three points, then the compass Â which in this case represented by the reporter had identified himself as part of the Muhammadiyah. In doing news about Muhammadiyah Congress, journalists tend to bring out the themes of good and using the words positive connotation. While in Congress proclaim the Nahdlatul Ulama, there was some news that gave rise to unfavorable theme of the NU and use words negative connotation.